2019
DOI: 10.1186/s13000-019-0833-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome and prognostic factors in PCNSL

Abstract: Objectives Standard treatment with a thiotepa-based regimen in countries with a limited resource is less feasible. Aims of the study were to evaluate the treatment outcome, and identify the prognostic factors in patients with primary central nervous system lymphoma (PCNSL). Methods We conducted a retrospective study of 43 patients diagnosed with PCNSL, DLBCL subtype, who were treated with either HDMTX-based regimen, whole brain radiotherapy (WBRT), or both between 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…BCL2 expression not related to t(14;18) (q32;q21) is frequent (Deckert, Brunn, et al., 2014; Deckert, Brunn, et al., 2014). Similar to literature, in this cohort most patients presented overexpression of BCL2 protein (80%), which a tendency for association with poor prognosis (worse OS and PFS; p values = .067 and 0.083, respectively) (Cai et al., 2019; Montesinos‐Rongen et al., 2008; Niparuck et al., 2019). In pre‐rituximab era, BCL2 expression was considered a poor prognostic factor in NHL; however, the overexpression of BCL2 in the post‐rituximab era in DLBCL has shown no prognostic value (Mounier et al., 2003).…”
Section: Discussionsupporting
confidence: 87%
“…BCL2 expression not related to t(14;18) (q32;q21) is frequent (Deckert, Brunn, et al., 2014; Deckert, Brunn, et al., 2014). Similar to literature, in this cohort most patients presented overexpression of BCL2 protein (80%), which a tendency for association with poor prognosis (worse OS and PFS; p values = .067 and 0.083, respectively) (Cai et al., 2019; Montesinos‐Rongen et al., 2008; Niparuck et al., 2019). In pre‐rituximab era, BCL2 expression was considered a poor prognostic factor in NHL; however, the overexpression of BCL2 in the post‐rituximab era in DLBCL has shown no prognostic value (Mounier et al., 2003).…”
Section: Discussionsupporting
confidence: 87%
“…Performing WBRT after chemotherapy yields a better survival rate than chemotherapy alone. However, the incidence of radiotherapy-induced neurotoxicity increases in patients who have undergone combined therapy [ 7 - 9 ]. Therefore, precise prognostic factors are needed to develop improved risk-adapted treatment strategies, such as high-dose chemotherapy with autologous stem cell transplantation (auto-SCT) or chemotherapy, followed by WBRT in high-risk patients with PCNSL.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our data suggest that among treated PCNSL cases, a combined-modality therapy may be better at prolonging survival. A recent study of PCNSLs reported that a significantly prolonged survival could be achieved with a combined-modality therapy, although unlike in our study, autologous stem cell therapy was excluded 36 . Current treatment regimens for PCNSL remain ineffective partly because CNS is inaccessible to many drugs.…”
Section: Discussionmentioning
confidence: 75%